A study on the mediating role of experiencescapes in tourists’ alcohol consumption / Edgar D’Souza and M.S. Dayanand - D’Souza, Edgar; Dayanand, M.S. (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
In a tourist's search to escape from the usual routine, alcohol consumption forms a critical part of the tourism experience. It is just an incidental accompaniment of the journey for some travellers, but for others, it is the key reason to travel. Just like dining at restaurants, beverage consumption has become a status symbol. People are looking for experiences that go beyond the food and beverage itself, and they use the food and beverage outlets as an arena where they can relax, enjoy and socialize. While our earlier studies have examined the influence of tourists' knowledge and past experiences regarding alcohol consumption on the choice of alcoholic beverages and factors affecting the choice of drinkscapes at tourist destinations. This study has investigated the mediating impact of experiencescapes (drinkscapes, social setting and the service experience) on the overall alcohol consumption experience using quantitative techniques. It has also investigated if tourist's demographics have a moderating effect on the relationship between alcohol consumption experience and future behavioural intentions. Results indicated that while that the choice of drinkscapes does not mediate the positive impact of the choice of alcohol on the alcohol consumption experience, social settings and the service experience did.